2021
DOI: 10.1016/j.celrep.2021.108974
|View full text |Cite
|
Sign up to set email alerts
|

High-dimensional profiling clusters asthma severity by lymphoid and non-lymphoid status

Abstract: Asthma is an immune-mediated heterogeneous disease. Current type-2 biomarkers provide limited understanding of underlying pathobiology or therapeutic guidance. Using a multi-omics approach, Camiolo et al. identify two clusters of severe asthma patients with similar type-2 biomarkers but with strikingly distinct immune profiles and associated biological pathways.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
38
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(39 citation statements)
references
References 75 publications
(85 reference statements)
1
38
0
Order By: Relevance
“…In our recent work with the IMSA cohort, we identified a subset of patients with SA characterized by enrichment of IFN-γ + T cells in their BAL fluid in whom IL-18 may be an upstream regulator ( 52 ). It is important to note that these patients also displayed concomitant T2 inflammation, which was indistinguishable from those without the high T1 phenotype.…”
Section: Discussionmentioning
confidence: 99%
“…In our recent work with the IMSA cohort, we identified a subset of patients with SA characterized by enrichment of IFN-γ + T cells in their BAL fluid in whom IL-18 may be an upstream regulator ( 52 ). It is important to note that these patients also displayed concomitant T2 inflammation, which was indistinguishable from those without the high T1 phenotype.…”
Section: Discussionmentioning
confidence: 99%
“…Applying mass cytometry and machine learning to BAL cells from corticosteroid‐resistant asthma generated two clusters: one enriched in IL‐4+ innate immune cells and another dominated by IFN‐γ+ T cells, including tissue‐resident memory cells. The immune cell linkage developed through Exploratory Matrices (ICLite) algorithm showed signatures of mitosis and IL‐7 signalling in CD206‐FcεRI+CD127+IL‐4+ innate cells in the first cluster, and adaptive immune responses in T cells in the other 84 …”
Section: Precision Medicine In Asthma—biomarkers and Novel Toolsmentioning
confidence: 99%
“…from corticosteroid-resistant asthma generated two clusters: one enriched in IL-4+ innate immune cells and another dominated by IFN-γ+ T cells, including tissue-resident memory cells. The immune cell linkage developed through Exploratory Matrices (ICLite) algorithm showed signatures of mitosis and IL-7 signalling in CD206-FcεRI+CD127+IL-4+ innate cells in the first cluster, and adaptive immune responses in T cells in the other 84. Merged Affinity Network Association Clustering (MANAclust) is a coding-free, automated pipeline enabling integration of categorical and numeric data spanning clinical and multi-omic profiles for unsupervised clustering to identify disease subsets.…”
mentioning
confidence: 99%
“… 51 Importantly, our recent study of human severe asthma has identified lung macrophages expressing the Type 2 cytokine IL-4 in a subset of these patients whose airways were enriched in IL-4+ innate immune cells. 52 It stands to reason, therefore, that tolerance induces a contraction of both DC and macrophage numbers in the lungs.…”
Section: Discussionmentioning
confidence: 99%